(untitled) (African Journal of Biomedical Research, 2022)
Spondias mombin is one of the species belonging to the (Family: Anacardiaceae), its ethnomedicinal uses may be justified through many studies that reported potential pharmacological properties due to its phytochemical compounds. This review aimed at examining the ethnomedicinal uses, phytochemical compounds and pharmacological properties of S. mombin leaf extracts on the African continent, to justify its use in the management and/ or treatment of viral infections and cancers. Electronic databases such as Google Scholar, SciHub, PubMed and Science Direct with search dates between 1999 and 2019 were used. Findings from this review confirm the ethnomedicinal uses, of decoctions and infusions of S. mombin leaf extracts for management diseases such as malaria, sore throat, and inflammation disorders; studies confirmed the presence of phytochemical compounds such as Geraniin, 2-O-Caffeoyl-(+)-allohydroxycitric acid, Quercetin-3-O-β-D-glucopyranoside and pelandjuaic acid, responsible for the antiviral and chemotherapeutic properties. However, there is a need for bio-assay guided extractions, isolation, identification and characterization of phytochemical compound(s) in the leaf extracts of S. mombin that may be responsible for antiviral and anticancer activity. Investigations of the pharmacological action, in silico and in vitro studies of known and /or newly isolated compounds are warranted in the management and /or treatment of viral infections such as, Severe Acute Respiratory Syndrome Coronavirus 2, and cancers to justify the use of leaf extracts of S. mombin on the African continent for the management of viral infections and or cancer.